Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1016/j.invent.2019.100258
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of face-to-face and online training in improving managers' confidence to support the mental health of workers

Abstract: BackgroundIn recognition of the important role managers play in the well-being of the staff they supervise, many workplaces are implementing specialised training for leaders to help them better understand and support the mental health needs of their staff. This training can be delivered through face-to-face or online training sessions. Evaluation of such programs have found positive results for each format when compared to a control group, but to date, face-to-face and online manager mental health training hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 31 publications
(40 reference statements)
2
32
0
Order By: Relevance
“…By having regular conversations with their workers about what they value in work and what their needs are to realize those work values, supervisors can support job crafting and prevent 'reversed job crafting' that was found in the long-term group. The finding that managers play a key role in the RTW process and that improved communication is associated with faster RTW has also been found by others [41][42][43]. However, whereas managers may acknowledge the importance of communication about mental wellbeing, several studies have shown they often feel uncertain about how to best support workers' mental wellbeing needs [42,44], and they do not always see it as their responsibility to start the conversation with the worker [45].…”
Section: Discussionmentioning
confidence: 82%
“…By having regular conversations with their workers about what they value in work and what their needs are to realize those work values, supervisors can support job crafting and prevent 'reversed job crafting' that was found in the long-term group. The finding that managers play a key role in the RTW process and that improved communication is associated with faster RTW has also been found by others [41][42][43]. However, whereas managers may acknowledge the importance of communication about mental wellbeing, several studies have shown they often feel uncertain about how to best support workers' mental wellbeing needs [42,44], and they do not always see it as their responsibility to start the conversation with the worker [45].…”
Section: Discussionmentioning
confidence: 82%
“…Some of researches are oriented to the business organizations including in support relationship between managers and their employees. For instance, Gayed et al (2019) provide a comparison between online and traditional (face to face) training in the complex business context. The authors try to understand and analyze the different types of trainings in line of the improvement the level of managers` confidence, which on his side to support the mental health of the employees.…”
Section: Literature Overviewmentioning
confidence: 99%
“…Both modes of delivery appear able to create sustained changes in confidence levels. However, a key challenge of online modes of delivery appears to be retention rates and program adherence (Gayed et al, 2019). The researchers have presented as well one of the possible solutions that could lead to overcoming this identified problem: Additional strategies involving more engaging means of improving retention in online training need to be determined to maximize the impact of new online training programs (ibid).…”
Section: Literature Overviewmentioning
confidence: 99%
“…Our findings are consistent with those of (Aggarwal et al, 2011) that compared online training and traditional face-to-face approaches in the delivery of information to students in India, with similar results found for face-to-face and online delivery. Gayed et al (2019) in their Australian study that compared face-to-face and online approaches to deliver training, aimed at improving managers' communication with staff about mental health issues, also found that both training methods had similar effects on confidence.…”
Section: Discussionmentioning
confidence: 96%
“…An Australian study compared face-to-face and online approaches to deliver training aimed at improving managers' communication with staff about mental health issues (Gayed et al, 2019). The authors reported that both training approaches improved confidence and that this was sustained at follow-up.…”
Section: Introductionmentioning
confidence: 99%